A Study on Adsorption Capacity of Activated Carbons through Analysis of Variance (Anova) - Govindasami, S; Sivakumar, D; B Sakthivel, P (International Journal of Engineering and Technology, 2018)
Recycling and reusing the waste is one of the agenda of sustainable development. Hence this investigation was carried out on utilizing the industrial sludge as activated carbon. The sludge was collected from treatment unit of sugar mill industry, paper mill industry and tannery industry and activated carbon was prepared and named as sugar mill sludge activated carbon (SSAC), paper mill sludge activated carbon (PSAC) and tannery industry sludge activated carbon (TSAC). Batch studies were performed between dye solution and activated carbon to determine adsorption capacity of adsorbent and optimum contact time for the contact process. The optimum contact time and optimum dosage was found to be 120 min and 3.0 g respectively. The maximum adsorption capacity of SSAC, PSAC & TSAC on the concentrations of 10 mg/l of reactive dye solution for the dosage of 3.0 g was 100 %, 92.88 % and 88.54 %. The experimental data and analysis was checked by ANOVA table analysis to justify mathematically. As per ANOVA table the mean performance of SSAC is higher and TSAC is lower. So, finally it is concluded that the experimental results are justified by the ANOVA table analysis on the adsorption capacity of activated carbons.Â Â Â